Biogeographic trends of endemic and subendemic flora in the western Iberian Peninsula under scenarios of future climate changes - Rocha, João; Almeida da Silva, Rubim; Amich, Francisco; Martins, Álvaro; Almeida, Paulo; Aranha, José T.; Garcia-Cabral, Isabel; Martins, Mónica; Castro, Carlos; Crespí, António L. (Lazaroa, 2014)
Altitude, temperature and precipitation are important environmental variables in the circumscription of endemic plants’ biogeographic distributions. Taking in account their present distribution, this work studies the distribution trends of 116 endemic and subendemic species that occur on the western Iberian Peninsula and north-western Morocco, in different scenarios of future climate change. It was possible to identify five groups of taxa in the present environmental conditions, four of which for the northern part of the Iberian Peninsula. This range can partially be explained by the altitudinal variability of such area. The other group distributes along the western of the Iberian Peninsula. Concerning future climate change scenarios, important changes in species distribution, and a general south-north trend were obtained. Under harsher climatic changes, only the groups that tolerate the most variable environmental conditions persist. Estimates of extinction rates of the studied taxa for the next 75 years scenarios are also presented. The present methodology allow the application of ecological indicators (environmental groups, in this case) to characterize bioclimatic trends.